Comparison of the Roles of Calcineurin in Physiology and Virulence in Serotype D and Serotype A Strains of Cryptococcus neoformans - Cruz, M. Cristina (American Society for Microbiology, 2000)
The calcineurin gene was cloned and disrupted in serotype D strains of Cryptococcus neoformans. Serotype A and serotype D calcineurin mutants were inviable at 37°C and avirulent in mice, whereas only serotype A mutants were cation stress sensitive. Thus, calcineurin plays conserved and divergent roles in serotype A and serotype D strains.